2012
DOI: 10.1007/s13258-011-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic rearrangement between wheat and Thinopyrum elongatum revealed by mapped functional molecular markers

Abstract: Thinopyrum elongatum serves as an excellent gene pool for wheat improvement. Genes for resistance to many biotic and abiotic stresses have been transferred from Th. elongatum to wheat through chromosome manipulation. For breeding programs, molecular markers enable screening of a large number of genotypes for alien chromosome introgressions. The main objective of the present study was to develop and characterize EST (expressed sequence tags) and PLUG (PCR-based Landmark Unique Gene) markers that can distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…Our previous studies showed that the PLUG markers were useful for producing alien chromosome-specific markers , Hu et al, 2012. A total of 12 PLUG markers from wheat homologous group 2 were tested on D11-5 compared to its parents MY11 and TDH-2 ( table 1 ).…”
Section: Molecular Marker Analysismentioning
confidence: 99%
“…Our previous studies showed that the PLUG markers were useful for producing alien chromosome-specific markers , Hu et al, 2012. A total of 12 PLUG markers from wheat homologous group 2 were tested on D11-5 compared to its parents MY11 and TDH-2 ( table 1 ).…”
Section: Molecular Marker Analysismentioning
confidence: 99%
“…uniaristata , Th. intermedium [Li et al, 2013], and Lophopyrum elongatum [Hu et al, 2012]. However, markers specific for Ae.…”
Section: Discussionmentioning
confidence: 98%
“…The PLUG-PCR protocol followed Hu et al [2012]. In order to obtain high levels of polymorphisms, the PCR products were digested with the 4-base cutter enzymes Hae III and Taq I according to Ishikawa et al [2007] and were separated on 2% agarose gels.…”
Section: Dna Isolation and Est-based Pcrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the earlier studies, the PLUG markers were used in wheat for identification chromatin of distant genetic species Thinopyrum elongatum [15], Th. intermedium [16], Leymus mollis [17], Th.…”
Section: Variety Testingmentioning
confidence: 99%